The meaning and practice of stewardship in South Africa - Cockburn, Jessica; Cundill, Georgina; Shackleton, Sheona; Rouget, Mathieu (South African Journal of Science, 2019)
Stewardship offers a means of addressing social-ecological sustainability challenges, from the local to the global level. The concept of stewardship has had various meanings attached to it over time, and the links between the theory and practice of stewardship are not well understood. We sought to characterise the practice of stewardship in South Africa, to better understand the relationship between theory and practice. We found that practitioners’ understandings of stewardship coalesce around two core notions: the idea of stewardship as ‘responsible use and care’ of nature, and stewardship as a ‘balancing act’ between stewards’ use of natural resources for agricultural production and their responsibility to protect and manage the wider ecosystem. Stewardship practice in South Africa is strongly influenced by the biodiversity stewardship tool; however, many practitioners are integrating biodiversity stewardship with other approaches. These emerging social-ecological stewardship initiatives operate at landscape-level and work towards integrated social and ecological stewardship outcomes, by facilitating collaboration among diverse stakeholders. Further research is needed to better understand what is required to support these integrated, collaborative and cross-sectoral initiatives. Policy mechanisms that facilitate integrated place-based stewardship practice can contribute to expanding the practice of biodiversity stewardship in South Africa.Significance:• Our findings contribute to a growing understanding of what stewardship looks like in South Africa and how it is put into practice.• We show that biodiversity stewardship is a prevalent understanding of stewardship practice in South Africa and is often combined with other approaches for sustainable landscape management.• A broader understanding of stewardship, for example through the concept of social-ecological stewardship, can enable more integrated, collaborative approaches to landscape management, addressing the wide range of environmental and social development challenges faced in rural landscapes across South Africa.